The blind side [videorecording] - Netter, Gil (Warner Home Video, 2010)
Michael Oher is a homeless African-American teenager who is from a broken home. Mike is taken in by the Touhys, a well-to-do white family who help him fulfill his potential. At the same time, Oher?s presence in the Touhys? lives leads them to some insightful self-discoveries of their own. Living in his new environment, Mike faces a completely different set of challenges to overcome-- as both a football player and student. Mike works hard and, with the help of his coaches and adopted family, becomes an All-American offensive left tackle.